Predictive maintenance on machine using failure mode effect analysis - Vico Willy Vilardo; Firman (Operations Management and Information System Studies, 2021)
Industrial manufacturing company is a company whose main result in the production proccess are in the form of product. To expedite the company’s production activities supported by adequate machinery, so even with PT. X. But in maintenance activities, the Downtime that occurs exceeds the set downtime limit, which is 7,2% of 5% toleranacce limit. This study aims to find critical componenets of hammer mill machines baseed on one year engine failure history at PT. X using the Failure Mode Effecy and Analysis method. From the result of analysis there are 6 critical components of the hammer mill machine, namely: fixed blade, rotor blade, dynamo, V-Belt and gears.